THE STUDY OF CONVERSATIONAL IMPLICATURE IN A STAR IS BORN MOVIE - Febri Rhamadani, Siti Natasya; Arifin, M. Bahri; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
ABSTRACT This thesis studies conversational implicature in A Star is Born Movie. A Star Is Born is a 2018 American romantic musical drama film starred by Cooper, Lady Gaga, Dave Chappelle, Andrew Dice Clay, and Sam Elliott. It tells story about a hard-drinking musician (Cooper) who discovers and falls in love with a young singer (Gaga). The research focuses on the conversations between characters in the movie. The objectives of the study are 1) to identify the conversational implicatures utterances on A Star Is Born movie, and 2) to analyze the conversational implicatures  which have additional meaning. This research is a qualitative research. To analyze the data, the study uses Grice’s theory of conversational implicature; Generalized conversational implicature and particularized conversational implicature. The result of the study shows that: First, there are 375 data containing conversational implicature. Those conversational implicature divided into two, generalized implicature and particularized implicature. From 375 conversational implicature, there are 220 utterance belong to generalized implicature and 155 utterances belong to particularized implicature. Second, all conversational implicature have additional meaning. It means, there are 375 data of conversational implicature have additional meaning.Keywords: implicature, conversation, movie ABSTRAK Penelitian ini membahas implikatur percakapan dalam sebuah film berjudul A Star is Born. Film ini adalah sebuah film  drama romantis dari Amerika yang dibintangi  oleh Cooper, Lady Gaga, Dave Chappelle, Andrew Dice Clay, dan Sam Elliot. Film ini menceritakan seorang pemain music yang suka minum-minuman keras (Cooper) yang bertemu dan jatuh cinta pada seorang penyanyi muda (Lady Gaga). Penelitian berfokus pada percakapan antar karakter dalam film. Tujuan penelitian ini adalah 1) mengidentifikasi ujaran mana saja yang mengandung implikatur percakapan di film berjudul A Star Is Born, dan 2) menganalisa mana saja implikatur percakapan yang mempunyai makna tersirat. Penelitian ini adalah penelitian kualitatif. Untuk menganalisa data dipergunakan teori dari implikatur percakapan dari Grice, implikatur percakapan umum dan implikatur percakapan khusus. Hasil penelitian menunjukkan bahwa: Pertama, ada 375 implikatur percakapan. Implikatur percakapan tersebut terbagi dua yaitu implikatur percakapan umum dan implikatur percakapan khusus. Dari 375 implikatur percakapan, ada 220 ujaran yang dikategorikan sebagai implikatur percakapan umum dan 155 ujaran yang termasuk implikatur percakapan khusus. Kedua, semua implilkatur percakapan mempunyai makna tersirat yang berarti bahwa ada 273 data implikatur percakapan yang mempunyai makna tersirat.Kata kunci: implikatur, percakapan, film